2010
DOI: 10.1007/s11596-010-0463-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for patients after curative resection for proximal gastric cancer

Abstract: The factors influencing the long-term survival of patients with proximal gastric cancer (PGC) after curative resection were investigated. Data from 171 patients who underwent curative resection for PGC were retrospectively analyzed. The patients were grouped according to the clinicopathological factors and operative procedures. The tumor depth (T stage) and lymph node metastasis (pN stage) were graded according to the fifth edition of TNM Staging System published by UICC in 1997. The metastatic lymph node rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…Our study suggested an improved survival benefit of PG compared to TG among patients diagnosed with LAPGC. In contrast to early studies that have reported no differences in survival outcomes between the two surgical procedures (3,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) or a better survival was associated with TG procedure (22)(23)(24)(25). Varying patients' characteristics in different study populations might account for the inconsistent results.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Our study suggested an improved survival benefit of PG compared to TG among patients diagnosed with LAPGC. In contrast to early studies that have reported no differences in survival outcomes between the two surgical procedures (3,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) or a better survival was associated with TG procedure (22)(23)(24)(25). Varying patients' characteristics in different study populations might account for the inconsistent results.…”
Section: Discussioncontrasting
confidence: 58%
“…Several studies investigated overall survival (OS) of LAPGC patients who underwent TG or PG and reached inconsistent results. Some studies (3,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) reported that TG and PG had similar OS, whereas other studies (22)(23)(24)(25) showed that TG was associated with better 5-year OS than PG. Moreover, some studies even found that the prognosis of LAPGC patients undergoing PG was significantly better than those undergoing TG (9,26).…”
Section: Introductionmentioning
confidence: 99%
“…However, concerning to locally advanced PGC (LAPGC), it still has not reached a consensus. Proponents ( 10 , 16 , 17 ) of PG have argued that PG can achieve an equivalent overall survival (OS) compared to total gastrectomy (TG), whereas others ( 18 , 19 ) showed that TG was associated with better 5-year OS. Moreover, there was no clinical outcome of clinical randomized trial targeting the same issue.…”
Section: Introductionmentioning
confidence: 99%
“…The stomach was removed from the mouse, using an aseptic surgical procedure; the stomach cavity was cut along the greater curvature and ξ„„ushed with saline; and H. pylori eradication by rapid urease test and bacterial culture was observed. 21…”
Section: Detection Of Hp Eradicationmentioning
confidence: 99%